Signal detection and analysis of adverse events associated with Genvoya® based the FAERS database - Wang, Chengliang; Zhang, Yan; Tang, Xiting; Zhang, Guoping; Chen, Li (Frontiers in Pharmacology, 2024)
Objective: This study aims to evaluate and understand the safety profile of Genvoya® by mining and analyzing adverse drug event (ADE,adverse drug event) reports from the FDA Adverse Event Reporting System (FAERS,FDA Adverse Event Reporting System) database,thus providing valuable reference information for individuals infected with HIV.Methods: Data were obtained from the FAERS database,covering the period from the first quarter of 2015 to the fourth quarter of 2023,focusing on reports where Genvoya® was the primary suspected drug. Data import and extraction were conducted using MySQL 8.0,with adverse events standardized according to the Medical Dictionary for Regulatory Activities (MedDRA,Medical Dictionary for Regulatory Activities) 27.0 terminology. Potential adverse event signals were identified through disproportionality analysis,including the reporting odds ratio (ROR,reporting odds ratio) method and the comprehensive standard by the Medicines and Healthcare products Regulatory Agency (MHRA,Medicines and Healthcare products Regulatory Agency) method. Statistical analyses and graphical representations were performed.Results: A total of 2,376 adverse drug event reports related to Genvoya® were analyzed. Reports from male patients accounted for 74.33%,while those from female patients accounted for 22.39%. Common adverse events included weight gain,drug interactions,and increased viral load. Additionally,new potential adverse reactions,such as fat redistribution,HIV-associated neurocognitive disorders,and meningoencephalitis,were identified. These reactions were not adequately described in the existing literature and drug labels.Conclusion: Multiple adverse reactions were observed with the use of Genvoya®. Clinicians should closely monitor these reactions and implement necessary preventive and intervention measures based on patient-specific conditions and treatment guidelines.Although this study has limitations,the analysis of FAERS database data has revealed various potential risks associated with Genvoya®,providing important safety references for HIV treatment.